Analysis and Performance of ORC Based Solar Thermal Power Plant Using Benzene as a Working Fluid. (2016) - Kumar, Arun; Shukla, S.K.
Abstract: In the present scenario of huge demand of energy and economy create the necessity to give importance to all types of energy resources either it is conventional or nonconventional. Since the rapid consumption of fossil fuel over billions of people across the world are still unable to assess electricity. Furthermore, if the consumption of fossil fuel will be continued then our future generation will certainly have to face the shortage of it and the Global warming potential and ozone layer depletion will also increase. On account of this the Present paper investigates the application of benzene as a working fluid for ORC system. In this paper, performance analysis of organic Rankine cycle with benzene as working fluid has been done to improve efficiency and achieve better economy. This paper also describes clearly that if we want to produce 9 kW of power output with the same variation of mass flow rate as well as Reynolds number, the efficiency of ORC system will have to vary from 32.87% to 54.98% and that is possible only when the temperature at the outlet of turbine will be varied from 259.53 o C to 127.22 o C respectively. Since the fire point of benzene is very low and any instant sparking may cause hazard and hence in our system there is only a liquid to liquid heat transfer device. Boiler of ORC system consists of helical coil copper dipped into a thermal energy reservoir i.e. heat transfer fluid, therminol vp-1 whose upper temperature limit is 415 o C.